2010
DOI: 10.1371/journal.pbio.1000349
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Survival Role for Parkinson's Associated Gene DJ-1 Revealed in Trophically Impaired Dopaminergic Neurons

Abstract: A mouse genetic study reveals a novel cell-survival role for the Parkinson's disease-associated gene DJ-1 in dopaminergic neurons that have reduced support from endogenous survival factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 64 publications
(107 reference statements)
4
42
1
Order By: Relevance
“…Both parkin signaling and GDNF/RET signaling are required behaviors, such as movement, memory, motivation, and emotions (22,42). Consistent with this rationale, we could detect changes in motor and emotional behavior in RET KO and RET/parkin DKO mice (Figure 3), which we did not observe in previously reported RET and RET/DJ-1 KO mice (4,6). The lack of GDNF to stimulate mitochondrial biogenesis is in contrast to other trophic and neurotrophic factors, such as nerve growth factor (NGF), brain-derived neurotrophic factor, and EGF, for which this has been reported (43).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Both parkin signaling and GDNF/RET signaling are required behaviors, such as movement, memory, motivation, and emotions (22,42). Consistent with this rationale, we could detect changes in motor and emotional behavior in RET KO and RET/parkin DKO mice (Figure 3), which we did not observe in previously reported RET and RET/DJ-1 KO mice (4,6). The lack of GDNF to stimulate mitochondrial biogenesis is in contrast to other trophic and neurotrophic factors, such as nerve growth factor (NGF), brain-derived neurotrophic factor, and EGF, for which this has been reported (43).…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, in the RET-deficient background, DJ-1 seems to be essential only for DA cell body survival (6). Here, we found that parkin is important for cell body and axonal maintenance and has also a minor effect on dopamine levels in the striatum (Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Deletion and point mutations of DJ-1 have been shown to be responsible for onset of familial Parkinson's disease, PARK7 [5]. DJ-1 is a multi-functional protein and plays roles in transcriptional regulation [8][9][10][11][12][13][14][15] and in modulation of signaling cascades [16][17][18][19][20] through protein-protein interaction, leading to anti-oxidative stress function [21][22][23]. Furthermore, we have reported that DJ-1 activated TH and DDC through direct binding to TH and DDC in an oxidative status of DJ-1-dependent manner [24] and that human DJ-1 activates TH gene expression in cultured human dopaminergic cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…Increase in DJ-1 expression may be induced by ROS and DJ-1 overexpression specifically protects against dopamine toxicity (23,24); more specifically, a compensatory upregulation of DJ-1 and parkin has been reported in the brain of a A53T a-synuclein mouse model treated with the mitochondrial toxin rotenone (25); eventually, DJ-1 is indispensable for the survival of dopaminergic neurons lacking the GDNF-receptor Ret (26). DJ-1 appears thus to display a multifaceted function that is further regulated by the interaction with cytosolic and mitochondrial proteins (27).…”
Section: Resultsmentioning
confidence: 99%